(х²-3х)²-17(х²-3х)-18=0(через замену)

adilukanova adilukanova    3   27.06.2019 20:50    0

Ответы
sevi88 sevi88  02.10.2020 13:25
(x^{2}-3x)^{2}-17(x^{2}-3x)-18=0\\
x^{2}-3x=t\\
t^{2}-17t-18=0\\
t_{1}+t_{2}=17;\space t_{1}t_{2}=-18\\
\left[\begin{array}{l}
t=18\\
t=-1
\end{array}\right.\to
\left[\begin{array}{l}
x^{2}-3x=18\\
x^{2}-3x=-1
\end{array}\right.
\to
\left[\begin{array}{l}
\left[\begin{array}{l}
x=6\\
x=-3
\end{array}\right\\
\\
\left[\begin{array}{l}
x=\frac{3+\sqrt{5}}{2}\\
x=\frac{3-\sqrt{5}}{2}
\end{array}\right.
\end{array}\right.\\

ответ: -3; 6; \frac{3\pm \sqrt{5}}{2}.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра